Long-duration head-down tilt bed rest confirms the relevance of the neutrophil to lymphocyte ratio and suggests coupling it with the platelet to lymphocyte ratio to monitor the immune health of astronauts - Jacob, Pauline; Bonnefoy, Julie; Ghislin, Stéphanie; Frippiat, Jean-Pol (Frontiers in Immunology, 2022)
The identification of safe and easily-determined-inflight biomarkers to monitor the immune system of astronauts is mandatory to ensure their well-being and the success of the missions. In this report, we evaluated the relevance of two biomarkers whose determination could be easily implemented in a spacecraft in the near future by using bedridden volunteers as a ground-based model of the microgravity of spaceflight. Our data confirm the relevance of the neutrophil to lymphocyte ratio (NLR) and suggest platelet to lymphocyte ratio (PLR) monitoring to assess long-lasting immune diseases. We recommend coupling these ratios to other biomarkers, such as the quantification of cytokines and viral load measurements, to efficiently detect immune dysfunction, determine when countermeasures should be applied to promote immune recovery, prevent the development of disease, and track responses to treatment.